2018
DOI: 10.1073/pnas.1721815115
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage angiotensin II type 2 receptor triggers neuropathic pain

Abstract: Peripheral nerve damage initiates a complex series of structural and cellular processes that culminate in chronic neuropathic pain. The recent success of a type 2 angiotensin II (Ang II) receptor (AT2R) antagonist in a phase II clinical trial for the treatment of postherpetic neuralgia suggests angiotensin signaling is involved in neuropathic pain. However, transcriptome analysis indicates a lack of AT2R gene () expression in human and rodent sensory ganglia, raising questions regarding the tissue/cell target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
149
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(154 citation statements)
references
References 69 publications
4
149
1
Order By: Relevance
“…A recent report 21 took a different approach, using the macrophage Fas-induced apoptosis (MAFIA) transgenic mouse line 22 . As for the TK or DTR mice, this line expresses a suicide gene (Fas) under the control of the CSF1R promoter, which is specifically expressed in macrophages and microglia.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A recent report 21 took a different approach, using the macrophage Fas-induced apoptosis (MAFIA) transgenic mouse line 22 . As for the TK or DTR mice, this line expresses a suicide gene (Fas) under the control of the CSF1R promoter, which is specifically expressed in macrophages and microglia.…”
mentioning
confidence: 99%
“…Importantly, as this transgenic line coexpresses green fluorescent protein (GFP) under control of the same promoter, it is possible to monitor the distribution of cells that express the suicide gene and the extent of their depletion. Using the MAFIA mice, Shepherd et al 21 demonstrated reduced nerve injury-induced mechanical hypersensitivity, a hallmark of the neuropathic pain phenotype, after depletion of circulating monocytes and macrophages at the nerve injury site. Moreover, as these authors found that DRG macrophages were spared, they concluded that peripheral macrophages, but not those in the DRG, are the critical contributors to nerve injury-induced neuropathic pain 21 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…administration of Ang II causes hypersensitivity (Shepherd, Copits, et al, ). While it was suggested that the induction of neuropathic pain involves the activation of AT2 receptors in DRGs (Smith et al, ), other reports indicate that it involves AT2 receptors on peripheral macrophages (Shepherd, Copits, et al, ; Shepherd, Mickle, et al, ). As the action site of Ang II is still debated and requires further studies, we have investigated pain transmission from the perspective of the spinal Ang system.…”
Section: Resultsmentioning
confidence: 99%
“…Though it has the capacity to regenerate, the PNS is also prone to injury and degeneration (8). Studies of PNS injury have shown that PNS macrophages play important roles for debris clearance, pain development, and regeneration (9, 10, 11). While the contribution of recruited monocytes cannot be excluded, these studies demonstrate the importance of PNS macrophages in nerve injury.…”
Section: Introductionmentioning
confidence: 99%